International experience of public administration development: What can we learn from other countries? - Serhiivna Izbash, Kateryna; Balamush, Mariana Anatoliivna; Denysyuk, Stanislav; Miroshnychenko, Serhiy Serhiyovich (DIXI, 2020)
Objective: The purpose of the article is to analyze the study and the international experience of public administration in order to find the most effective one for Ukraine. Methodology: While writing the article, the following methods were used: Logical, semantic, documentary analysis, and comparative legal. Findings: Both positive and negative aspects of borrowing the international experience of developed countries in the field of public administration are considered in the article. The emphasis is placed on the importance of creating an effective system of public administration in the state as a mandatory requirement for its successful functioning. All activities of public authorities are based on the quality of public administration. First of all, these are the processes of organizing management activities and establishing reliable control over it. The definitions of “public administration” and “development of public administration” are provided. Conclusions: It is concluded that the importance of qualitative study of the positive experience of other countries in the field of public administration will save a lot of time and effort in creating similar processes in their own country, avoiding the mistakes of predecessors. They are based on a thorough study of the formulated strategies and ideas that have been successfully put into practice.